Answer:
The inverse of xy is yx.
Step-by-step explanation:
Given: xy
We need to find the inverse of xy.
To find inverse of an expression, we need to replace the variable x by y and y by x.
Given xy.
Now replace x by y and y by x, we get
yx
Therefore, the inverse of xy is yx.
Let me show you an example.
y = x - 2
To find the inverse function, replace x by y and y by x, we get
x = y - 2
It is an equation, to write the equation in terms of y, add 2 from both sides, we get
x + 2 = y -2 + 2
x + 2 = y
Therefore, y = x + 2